Analysis and Design of Mobile-Based Waste Management Applications Prototype Methods - et. al., Muhammad Arief Kusmawardani, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
As the time goes by, a rapid growth of human population would eventually lead to the increase of daily waste. A lack of awareness of the community to dispose of waste properly might further harm the surrounding environment. Many people have limited knowledge as to where the garbage is dumped. In regard to that case, an Android-based waste management application system is designed. The prototype method is built for the system. This application is meant to carry out waste disposal transactions that can be accessed on Android. Hopefully, this application could increase user’s interest in disposing the waste and able to increase public insight in distinguishing organic and non-organic waste. The purpose of this research is to keep the community environment clean and healthy.